Experience of implementing metagenomic next-generation sequencing in patients with suspected pulmonary infection in clinical practice - Yuting Lai; Binqi Chen; Sida Chen; Yan Shen (Scientific Reports)
Abstract Pulmonary infections remain a leading cause of infectious disease-related hospitalizations. Metagenomic next-generation sequencing (mNGS) has emerged as a promising diagnostic tool for identifying pathogens responsible for pulmonary infections. However, implementing mNGS in clinical practice presents several challenges. We conducted a retrospective analysis of 97 patients with suspected pulmonary infections who were admitted to our hospital and underwent mNGS alongside conventional microbiologic tests (CMT) over the past three years. We compared the diagnostic efficacy of mNGS versus CMT and assessed the clinical applications and challenges associated with mNGS in managing pulmonary infections. mNGS detected pathogens in 63.9% of cases, outperforming CMT (27.8%) and showing notable improvements in identifying Mycobacterium, fungal species, and rare pathogens. Antibiotic regimens were adjusted for 77.4% of patients with positive mNGS results, with clinical improvement observed in 93.5%. Of the 138 microbial strains initially identified by mNGS as possible pathogens, 65 (47.1%) were reclassified as colonizing organisms upon further clinical evaluation, including bacteria and fungi commonly associated with pulmonary infections. Notably, one patient was diagnosed with aspiration pneumonia due to oral anaerobes, which mNGS had categorized as normal microbial flora. In conclusion, mNGS serves as a valuable diagnostic approach for pulmonary infections, enhancing etiologic precision and informing patient management. Nevertheless, a comprehensive clinical interpretation of mNGS-identified microorganisms is essential to achieve accurate diagnosis.